The effectiveness of neuromuscular taping and combined therapeutic exercises in reducing pain and improving knee health in soccer players - Muawanah, Siti; Ismaningsih; Putra, Rezky Guna; Juariah, Siti; Oktariani, Eva; Agustiyawan; Wanita, Deinike; Azizan, Azliyana (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
This study aimed to determine how neuromuscular taping (NMT), isometric training, and core stability exercises could help male soccer students with jumper’s knees, aged 14 to 17, improve their well-being and agility. This quasi-experimental study employed a pre-test and post-test design with two groups, each consisting of fourteen participants (n=14 per group). The intervention group received isometric training and core stability exercises combined with additional Neuromuscular Taping (NMT), while the control group performed only isometric training and core stability exercises. Clinical data were collected before and after the intervention using the Visual Analog Scale (VAS) to assess pain and the Illinois Agility Test (IAT) to evaluate agility. Three times a week for five weeks, the 15-session treatment was conducted under constant safety supervision. Both groups showed lower VAS scores (control: 5.71±1.204 to 3.00±0.961, p=0.0001; intervention: 5.43±1.222 to 1.93±1.072, p<0.000) and higher IAT scores (control: 21.67±1.112 to 15.37±0.780, p<0.000; intervention: 21.67±1.112 to 14.72±0.766, p=0.0001). Significant post-treatment effects on VAS (p=0.033) were found by independent t-tests. The intervention group, which received NMT, isometric training, and core stability exercises, showed better results in terms of pain reduction and agility improvement for the jumper’s knee.